A COMPARATIVE STUDY ON THE ABILITY BETWEEN THE FIRST YEAR FEMALE AND MALE STUDENTS OF SMK PGRI PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Yesi Meriance Hasugian; Syofia Delfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to compared between ability of the first year female and male students of SMK PGRI Pekanbaru in comprehending Narrative texts. The number of population was 213 students divided into seven classes. The writer used cluster random sampling technique to determine the sample. The samples were 28 students. The needed data were taken from the students’ score in comprehending narrative texts. The test comprehends five narrative texts of which all text has six items or 30 items all together. The time allocation was 80 minutes. Based on the research finding, it can be found: first, the ability of the students is in good level. Second, the mean score of female students was higher than mean score of male students (71,17 % > 62%) in comprehending narrative texts. This research finding confirmed the theories that female students are better than male students in language learning. T-test formula proved that the differences of female and male scores were significant statistically.Key Words: Comparative, Ability, Comprehending, Narrative Text